Computer safety, reliability, and security : SAFECOMP 2019 workshops, ASSURE, DECSoS, SASSUR, STRIVE, and WAISE, Turku, Finland, September 10, 2019, proceedings /: SAFECOMP 2019 workshops, ASSURE, DECSoS, SASSUR, STRIVE, and WAISE, Turku, Finland, September 10, 2019, proceedings. ([2019]) - Unknown
No abstract available